"تأثير صيغ التمويل الإسلامي على تنوع نشاط قطاع المؤسسات الصغيرة والمتوسطة في الجزائر دراسة حالة بنك البركة الوادي " - علي جلول; يونس سوفية; عمار سليماني (جامعة الوادي University Of Eloued, 2024)
"يهدف هذا البحث إلى دراسة دور صيغ التمويل الإسلامي في تنمية وتطوير وتنويع قطاع نشاطات المؤسسات الصغيرة والمتوسطة في الجزائر، وذلك بدراسة حالة بنك البركة وكالة الوادي، حيث تزايد الاهتمام بالتمويل الإسلامي لما له من مميزات كالتنوع في التمويل، وتعتبر المؤسسات الصغيرة والمتوسطة بمثابة الأداة الأكثر نجاعة في تحقيق التنمية الاقتصادية والاجتماعية، سواء في الدول النامية أو المتقدمة من خلال زيادة حجم الاستثمار وتعظيم الناتج الداخلي الخام وتوفير فرص عمل جديدة، وبذلك أصبح تمويل هذه المؤسسات يمثل أهمية كبيرة بالنسبة للحكومات مما جعل هذه الحكومات تهتم بالتمويل الإسلامي. توصلت هذه الدراسة إلى أن للمؤسسات الصغيرة والمتوسطة دورا رئيسيا في تحقيق النمو الاقتصادي والتنمية الاجتماعية، وتتسم صيغ التمويل الإسلامي بالتنوع والمرونة والعدالة في توزيع الناتج بين أطراف المشروع، ويتعامل بنك البركة وكالة الوادي في تمويل المؤسسات الصغيرة والمتوسطة على المرابحة والإيجار المالي لأنهما أقل مخاطرة. " "The aim of this research is to study the role of Islamic finance instruments in the development and diversification of the small and medium-sized enterprises (SMEs) sector in Algeria, focusing on the case of Baraka Bank and Al Wadi Agency. Islamic finance has gained increasing attention due to its advantages such as financing diversity. SMEs are considered highly effective tools for achieving economic and social development in both developing and developed countries, contributing to increased investment, maximization of GDP, and the creation of new job opportunities. The study concludes that SMEs play a crucial role in economic growth and social development. Islamic finance instruments are characterized by diversity, flexibility, and fairness in profit distribution among project stakeholders. Baraka Bank and Al Wadi Agency engage in financing SMEs through profit-sharing and leasing arrangements, perceived as less risky approaches. "
Keywords: المؤسسات الصغيرة والمتوسطة – التمويل الإسلامي – صيغ التمويل الإسلامي; Small and Medium-sized Enterprises (SMEs); Islamic Finance; Islamic Finance Instruments.